Dehydroabietylamine-decorated imino-phenols: supramolecular gelation and gel phase selective detection of Fe3+, Cu2+ and Hg2+ ions under different experimental conditions. (19th April 2022) - Ghosh, Subhasis; Ghosh, Sumit; Baildya, Nabajyoti; Ghosh, Kumaresh
Abstract : Dehydroabietylamine-linked Schiff bases 1–3 have been synthesized, characterized and employed in metal ion sensing in a sol–gel medium. The compounds have a propensity for gel formation from aqueous organic solvents. Abstract : Dehydroabietylamine-linked Schiff bases 1–3 have been synthesized, characterized and deployed in metal ion sensing in a sol–gel medium. The compounds have a propensity for gel formation in aqueous organic solvents and all three Schiff bases exhibit gelation in 1, 4-dioxane-H2 O (4 : 1, v/v ). The thermoreversible and colored gels are mechanically strong as evidenced from the rheological studies. The magnitudes of G ′ for the gels of 1, 2 and 3 are observed to be 7.38, 5.13 and 6.93 times higher than those of the respective G ′′. The morphology of the gels varied from fibrous to a needle/rod-like arrangement with a change in substituent around the azo motif. Theoretical study highlights the different aggregation patterns of the gelators. The gels are responsive to Cu 2+, Fe 3+ and Hg 2+ over a series of different metal ions. Visual detection of these ions with different attributes are achieved in the gel phase although the absorption and emission spectra of 1–3 in solution are weakly perturbed in the presence of these ions. The detection of Fe 2+ has also been accomplished in the presence of an oxidizing agent.